Promoting equitable access to quality seeds: The impact of social and behaviour change interventions among smallholder rice farmers in Butaleja, Uganda - Bomuhangi, Allan; Yila, Jummai (International Rice Research Institute, 2025)
This endline evaluation assesses the impact of Social and Behaviour Change (SBC) interventions on equitable access to and adoption of quality rice varieties among smallholder farmers in Butaleja District, Uganda. Using a cross-sectional survey design with quasi-experimental methods, the analysis compares 298 treated farmers against 128 control farmers, supplemented by qualitative data from 7 focus group discussions and 13 key informant interviews. The findings highlighted a positive treatment effect across key metrics. Awareness of improved rice varieties reached 95% among treated farmers, compared with the 80% observed in the control group. Ninety-one (91%) percent of the farmers in the treatment group adopted at least one improved variety compared to 42% at baseline and 73% in the control group. This adoption was not only extensive but also intensive, as treated farmers allocated a larger land area to improved varieties (2.3 acres on average) compared to control farmers (1.7 acres). The interventions also induced a shift towards more intensive and knowledge-based production systems, evidenced by a markedly higher rate of inorganic fertilizer use among treated farmers (70%) compared to control groups (25%). The economic prediction is positive, with farmers forecasting a yield increase of 25.86% per acre attributable to the SBC strategies. Furthermore, the project achieved its equity objectives, successfully enhancing the participation of women and youth and fostering local networks for seed access and knowledge sharing, indicating a strong potential for sustaining these net benefits beyond the project's lifecycle.